Variable course of disease of rheumatoid arthritis-associated usual interstitial pneumonia compared to other subtypes. Issue 1 (December 2016) - Nurmi, Hanna; Purokivi, Minna; Kärkkäinen, Miia; Kettunen, Hannu-Pekka; Selander, Tuomas; Kaarteenaho, Riitta
Abstract Background In rheumatoid arthritis-associated interstitial lung disease (RA-ILD), occurring in 10 % of patients with patients with RA, usual interstitial pattern (UIP) has shown to associate with poor prognosis but more detailed data about the course of the disease in different subtypes is limited. Our aim was to compare the disease course of patients with RA-ILD categorized into either UIP or other types of ILDs. Methods Clinical and radiological information of 59 patients with RA-ILD were re-assessed and re-classified into UIP or non-UIP groups, followed by a between-group comparison of demographic data, lung function, survival, cause of death and comorbidities. Results The majority of patients (n = 35/59.3 %) showed a radiological UIP-like pattern in high resolution computed tomography. The median survival was 92 months (95 % CI 62.8–121.2) in the UIP-group and 137 months (95 % CI 31.0–243.0) in the non-UIP-group (p = 0.417). Differences in course of disease were found in the number of hospitalizations for respiratory reasons (mean 1.9 ± 2.6 in UIP vs. 0.5 ± 0.9 in non-UIP group, p = 0.004), the use of oxygen therapy (8/22.9 % UIP patients vs. 0 non-UIP patients, p = 0.016), number of deaths (23/65.7 % vs. 10/41.7 %, p = 0.046) and decline in diffusion capacity (56 ± 20.6 vs. 69 ± 20.2, p = 0.021). Dyspnea and inspiratory crackles were detected more often in the UIP group. RA-ILD was the most common primary cause of death (39.4 % of cases). Hypertension, coronary artery disease, chronic obstructive pulmonary disease, heart insufficiency, diabetes and asthma were common comorbidities. ILD preceded RA diagnosis in 13.6 % of patients. Conclusions The course of the disease in RA-UIP patients is different from the other RA-ILD subtypes. Several comorbidities associated commonly with RA-ILD, although ILD was the predominant primary cause of death.